Decontamination Training: With and Without Virtual Reality Simulation. (April 2015) - Farra, Sharon Lee; Smith, Sherrill; Gillespie, Gordon Lee; Nicely, Stephanie; Ulrich, Deborah L.; Hodgson, Eric; French, DeAnne
Abstract : Nurses must be prepared to care for patients following a disaster, including patients exposed to hazardous contaminants. The purpose of this study was to examine the use of virtual reality simulation (VRS) to teach the disaster-specific skill of decontamination. A quasi-experimental design was used to assign nursing students from 2 baccalaureate nursing programs to 1 of 2 groups to learn the disaster skill of decontamination—printed written directions or VRS. Performance, knowledge, and self-efficacy were outcome measures. Although students in the treatment group had significantly lower performance scores than the control group ( p = 0.004), students taking part in VRS completed the skill in a significantly shorter amount of time ( p = 0.008). No significant group differences were found for self-efficacy ( p = 0.172) or knowledge ( p = 0.631). However, students in the VRS treatment group reported high levels of satisfaction with VRS as a training method. The disaster-specific skill of decontamination is a low-volume, high-risk skill that must be performed with accuracy to protect both exposed patients and providers performing decontamination. As frontline providers for casualties following a disaster event, emergency nurses must be prepared to perform this skill when needed. Preparation requires cost-effective, timely, and evidence-based educational opportunities that promote positive outcomes. Further investigation is needed to determine the benefits and long-term effects of VRS for disaster education.